2007
DOI: 10.1016/j.molcel.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The Transamidosome: A Dynamic Ribonucleoprotein Particle Dedicated to Prokaryotic tRNA-Dependent Asparagine Biosynthesis

Abstract: Asparagine, one of the 22 genetically encoded amino acids, can be synthesized by a tRNA-dependent mechanism. So far, this type of pathway was believed to proceed via two independent steps. A nondiscriminating aspartyl-tRNA synthetase (ND-DRS) first generates a mischarged aspartyl-tRNAAsn that dissociates from the enzyme and binds to a tRNA-dependent amidotransferase (AdT), which then converts the tRNA-bound aspartate into asparagine. We show herein that the ND-DRS, tRNAAsn, and AdT assemble into a specific rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
138
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 27 publications
4
138
2
Order By: Relevance
“…In these processes, the nondiscriminating aaRSs (ND-aaRSs) charge tRNA Asn and tRNA Gln with Asp (24) and Glu (25), respectively; then they are converted to Asn-tRNA Asn (24,26) and Gln-tRNA Gln (27), respectively, by amidotransferases (AdTs). The ND-aaRSs and AdTs can form complexes called transamidosomes (28), which could allow channeling of the mischarged aa-tRNAs from the ND-aaRSs to the AdTs without dissociation from the complexes (29,30). Several different types of transamidosome and regulatory features have been discovered (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these processes, the nondiscriminating aaRSs (ND-aaRSs) charge tRNA Asn and tRNA Gln with Asp (24) and Glu (25), respectively; then they are converted to Asn-tRNA Asn (24,26) and Gln-tRNA Gln (27), respectively, by amidotransferases (AdTs). The ND-aaRSs and AdTs can form complexes called transamidosomes (28), which could allow channeling of the mischarged aa-tRNAs from the ND-aaRSs to the AdTs without dissociation from the complexes (29,30). Several different types of transamidosome and regulatory features have been discovered (31).…”
Section: Discussionmentioning
confidence: 99%
“…(i) The Asn transamidosome in Thermus thermophilus requires tRNA Asn as a scaffold for formation and is stable over the sequential reactions (28,29). It enhances the aminoacylation activity, protects the mischarged Asp-tRNA Asn from deacylation, and increases the overall production of Asn-tRNA Asn (28).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies in which a common tRNA is recognized by distinct tRNA synthetases, these data were interpreted to support a general hypothesis that aminoacyl-tRNA synthetases evolved in the context of preestablished tRNA identity. Other work on the M. jannaschii pathway has shown that SepRS and SepCysS form a stable binary complex that assists in conversion of the intermediate SeptRNA Cys to Cys-tRNA Cys , a complex reminiscent of the transamidosome particle that facilitates prokaryotic tRNA-dependent asparagine biosynthesis (11,12).…”
mentioning
confidence: 99%
“…6D). This suggests that the Plasmodium apicoplast may contain a tRNA Gln ⅐ND-GluRS⅐GatA⅐GatB complex, akin to the transamidosomes described in archaea (61) and the eubacterium T. thermophilus (84). Such a complex would prevent challenging the genetic code integrity as demonstrated for tRNA-dependent Asn formation (61).…”
Section: Discussionmentioning
confidence: 89%